2022
DOI: 10.3390/ijerph192214787
|View full text |Cite
|
Sign up to set email alerts
|

Diets, Dietary Patterns, Single Foods and Pancreatic Cancer Risk: An Umbrella Review of Meta-Analyses

Abstract: Pancreatic cancer (PC) represents the third leading cause of cancer death in 2020. Despite the fact that, in 2018, the World Cancer Research Fund report concluded that there is still a lack of evidence on the role of foods or diets and risk for PC, a flourishing body of evidence has been published and needs to be analyzed. For this reason, we conducted an umbrella review on the association between different dietary patterns/food components and PC. Data sources PubMed/MEDLINE, Scopus, Web of Science, EMBASE, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
(209 reference statements)
2
10
0
Order By: Relevance
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 83%
“…However, there may be considerable correlations between the certainty of the results of the evidence and the results of quality assessments based on AMSTAR 2. Recently, many umbrella reviews have been performed that used both AMSTAR 2 and GRADE in healthcare settings [22,25,27,[32][33][34]. These studies were consistently determined to be "low" and "very low" according to the GRADE evaluation when the ratings were also "low" or "critically low" in AMSTAR 2.…”
Section: Relevance To the Grade Approach (Grading Of Recommendations ...mentioning
confidence: 99%
“…Conversely, high intake of red meat was associated with increased risk of pancreatic cancer. However, the general quality of evidence was low to critically low (26). Similar results were obtained in a multi case-control study published shortly after the umbrella review.…”
Section: Discussionsupporting
confidence: 63%
“…The umbrella review by Gianfredi et al [ 59 ], did describe a lower risk of pancreatic cancer associated with vegetarian diets.…”
Section: Resultsmentioning
confidence: 99%